Gender Dimensions of Trade Facilitation and Logistics : A Guidance Note - Higgins, Kate (Washington, DC, 2014)
Gender equality is a vital instrument for development. In trade related interventions, taking gender equality into account not only spurs country competitiveness, but also helps obtain better outcomes. The World Bank's international trade department and the gender and development unit in the Poverty Reduction and Economic Management network are collaborating to produce guidance notes in order to help people working in the field identify and assess the gender dimensions of trade projects. This guidance note focuses on trade facilitation and logistics initiatives, which seek to improve customs and border management, trade infrastructure, port efficiency, transport security, logistics and transport services, regional trade corridors and transit and multimodal transport. The guidance note demonstrates why gender matters for trade facilitation and logistics and how gender dimensions can be integrated into trade facilitation and logistics initiatives. The ultimate objective of the note is to support World Bank staff to enhance the effectiveness of the World Banks's trade-related work by integrating a gender perspective into trade-related policy dialogue, and the design, implementation and monitoring and evaluation of trade facilitation and logistics initiatives.